2022-RA-1521-ESGO Do exophytic and endophytic patterns in borderline ovarian tumors have different prognostic implications? A large multicentric experience. (20th October 2022) - Capozzi, Vito Andrea; Scarpelli, Elisa; Monfardini, Luciano; Gaiano, Michela; Armano, Giulia; Butera, Diana; Barresi, Giuseppe; Rotondella, Isabella; de Finis, Alessandra; Scebba, Davide; Uccella, Stefano; Mandato, Vincenzo Dario; et al.
Abstract : Introduction/Background: Borderline ovarian tumor (BOT) is a non-invasive tumor with a favourable prognosis. Depending on tumor pathologic aspect, two patterns of growth can be identified: endophytic and exophytic pattern. Concerns have arisen about the clinical significance of BOT with exophytic growth pattern. This study aims to analyse and compare patients' characteristics, sonographic features, and prognosis related to both patterns. Methodology: A retrospective multicentre study was conducted. Patients who underwent surgical treatment for BOT were recruited and they were divided in two groups according to macroscopic aspect. Results: Of the 229 patients who met the inclusion criteria, 169 (73.8%) were in the endophytic group and 60 (26.2%) in the exophytic group. Patients in the endophytic group were older (50 vs. 41 years, p=0.001), less frequently nulliparous women (38.5% vs. 58.3%, p=0.008), more often with BMI ≥ 30 Kg/m 2 (17.8% vs 5%, p=0.0116). The endophytic pattern was associated with mucinous histology (p 0, 001), an earlier FIGO stage (p<0.001), and more often a maximum lesion diameter > 100 mm (p=0.043). The exophytic pattern was associated with serous histology (p<0.001), presence of peritoneal implants (p<0.001), tumor cells in peritoneal washing (p<0.001) and abnormal Ca125 (p=0.003). Kaplan Meier curves showed no significant differences (p=0.076) in DFS at 1-year (99.4 vs. 94.5%), 3-year (98.6 vs. 91.9%), and 5-year (96.5 vs. 82.2%). Furthermore, recurrence status was associated with the median age (p=0.001), FIGO stage (p=0.002), and fertility-sparing surgery (p=0.001) but not with the tumor histology (p=0.215). Conclusion: The study delineated two different patient profiles related to the tumor pattern of growth. The exophytic pattern was associated with the presence of invasive and non-invasive peritoneal implants, an advanced FIGO stage, without impact on DFS. Identification of the BOT pattern during preoperative workup could be useful for better surgical planning.